2017
DOI: 10.3349/ymj.2017.58.4.867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Plasma Exchange on Survival in Patients with Severe Fever with Thrombocytopenia Syndrome: A Multicenter Study

Abstract: Despite a high mortality rate, no specific treatment for severe fever with thrombocytopenia syndrome (SFTS) has been established. This study compared the clinical outcomes of SFTS patients treated with plasma exchange (PE group) with those who were not treated (non-PE group) at nine Korean hospitals between May 2013 and August 2015. A total of 53 SFTS patients were included: 24 (45.3%) PE cases and 29 (54.7%) non-PE cases. The overall in-hospital mortality rate was 32.1% (17/53). The in-hospital mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
0
24
0
2
Order By: Relevance
“…A recent article from South Korea reported that early implementation of PE within 7 days of symptom onset was independently associated with 30-day mortality (adjusted hazard ratio 0.05, P value = 0.02). 2 Because PE reduces cytokine levels rather than viral loads (Figure 1), we believe that PE to reduce initial cytokine levels might be more beneficial during the early course of disease than during the later course. Further studies are needed to determine whether early PE can prevent organ damage by lowering cytokines in animal models mimicking human SFTS infection, as well as in clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…A recent article from South Korea reported that early implementation of PE within 7 days of symptom onset was independently associated with 30-day mortality (adjusted hazard ratio 0.05, P value = 0.02). 2 Because PE reduces cytokine levels rather than viral loads (Figure 1), we believe that PE to reduce initial cytokine levels might be more beneficial during the early course of disease than during the later course. Further studies are needed to determine whether early PE can prevent organ damage by lowering cytokines in animal models mimicking human SFTS infection, as well as in clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, there are no US Food and Drug Administration (FDA)-approved therapies or vaccines available to counter bunyaviral infections. Most clinical treatments are limited to therapeutic plasma exchange (Oh et al, 2017) and supportive care. A standard nucleoside analog class of inhibitors, such as ribavirin and favipiravir, has been tested for antiviral activities against SFTSV and HRTV infections, as they have been tested experimentally for other bunyaviral infections, including Hantaan virus (HTNV), Crimean Congo hemorrhagic fever virus (CCHFV), and Rift Valley Fever virus (RVFV) (Beaucourt and Vignuzzi, 2014;Delang et al, 2018;Tani et al, 2018;Westover et al, 2017).…”
Section: In Briefmentioning
confidence: 99%
“…Korean scientists have recently reported the SFTS patients successfully treated with plasma exchange (PE) with or without ribavirin administration [42e44]. Furthermore, the efficacy of plasma exchange in the treatment of SFTS was evaluated with 53 SFTS patients, in whom 24 and 29 patients were treated with and without plasma exchange, respectively [45]. The mortality rate of the PE group did not differ from that of the non-PE group.…”
Section: Plasma Exchangementioning
confidence: 99%